(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article presents the Argentine Juana (Joana) Paula Manso de Noronha during the period she lived in Rio de Janeiro, between 1840 and 1859, and worked as a journalist, educating, novelist, but mainly as a playwright and actress. Joana worked at the São Pedro de Alcântara Theater and at the Ginásio Dramático. She wrote four plays between dramas and comedy, and can be considered the first “Brazilian” female playwright of relevance in the history of national theater.